Analysis of social support network among civil servants in Oyo State, secretariat Ibadan. (2000)
Analysis of social support networks of young adults was conducted on the basis of two scales. The Visual Analog Scale (VAS) and the Whom Do You Turn To Scale (WDYTT) among 150 Junior and Senior Civil Servants of the Oyo State secretariat Ibadan. Their mean (X) age was 37.5 while the Standard Deviation (SD) was 15.1. The VAS and WDYTT scale were used to assess the extend of variation in the social network in the adult period of the life cycle. That is, a Visual Analog Scale (VAS) assesses the extent of closeness for seven interpersonal relationships and a second scale determining to whom the respondents would turn to in 14 situations (WDYTT). Chi-Square-test and t-test analyses were employed. The result showed significant differences, between the best female friend mother etc. Family of orientation vs friends as well as intergenerational vs intra generational were also compared on WDYTT scale. Result also showed significant difference on the friends (interpersonal as first and second choice. The implication and recommendation of the study were made on the need for further researches on social network and relationship across the life-span in Nigeria.